Pengaruh Kepatuhan, Pemeriksaan Dan Penagihan Pajak Terhadap Penerimaan Pajak Penghasilan Pasal 21 Badan Pada KPP Pratama Kedaton Di Bandar Lampung - Putih Rahmawati; Kusnadi Kusnadi; Hardini Ariningrum (Universitas Malahayati, 2016)
To the effect this research is subject to be determine assessable compliance influence, taxescheck and taxes billing to section income tax acceptance 21 on Taxeses Ministering Office PratamaKedaton Lampung's Port period 2011-2012. Population in observational it is exhaustive assessablebody which pay active its employee Income Tax on Taxeses Ministering Office Pratama Kedaton.Gathered data by surveys, documentation, and nonperilaku's observation. Regression model that isutilized have accomplished classic assumption quiz. analisis's tech data that is utilized is tech analisisbifilar linear regression. Base Quiz result t acknowledged that compliance and influential taxes billingsignifikan to section Income Tax acceptance 21 but probing taxeses not signifikan's ascendants tosection Income Tax acceptances 21. Base Quiz f compliance, check and ala taxes billing simultanhaving for signifikan to section income tax acceptance 21 on KPP Pratama Kedaton period 2011-2012. There is factor even the most dominant influential is taxes billing factor.